Mobilidade rural‑urbana e desigualdades étnico‑raciais e de Gênero no Acesso ao Auxílio Emergencial durante Governo Bolsonaro - Lorena Lima de Moraes; Shana Sampaio Sieber; Rebeca Mascarenhas Fonseca Barreto; Nicole Louise Macedo Teles de Pontes; Tatiane Vieira Barros (L'Ordinaire des Amériques)
The poor distribution of income in Brazil makes access to basic rights difficult, leading part of the population to live in poverty and social vulnerability, especially in the Northeast and North regions. The Covid-19 pandemic has further highlighted these inequalities, expressed in the difficulty of mobility to guarantee access to emergency policies, such as emergency aid. Thus, the social isolation of millions of people aggravated the economic losses and, although the Emergency Aid has alleviated this situation, the difficulty of access highlighted the mobility challenges faced by rural populations in these regions. This article focuses on discussing gender issues and socio-spatial inequalities experienced by Northeastern women from traditional communities and family farming in the Northeast, considering mobility as a central element for effective access to Emergency Assistance. To this end, we interviewed 74 women who highlighted rural-urban mobility as an obstacle to accessing social policies, in addition to exposure to the risk of contamination by the coronavirus. We conclude that the federal government’s disregard for poor, rural, black populations and especially inner-cities women, was configured under the aegis of State violence.